A New ZVT Quadratic High Step‐Up Nonisolated DC‐DC Converter - Abdollahi, Alireza; Delshad, Majid; Sadeghi, Ramtin (Journal of Engineering, 2025)
This paper introduces a quadratic DC‐DC converter that operates with zero‐voltage transition. In this converter, the combination of integrated coupled inductor technique and diode–capacitor technique is employed to boost static gain and decrease voltage stress on the main switch. Moreover, with the help of a third winding wound on the main ferrite core and an auxiliary switch and diode, zero voltage transitions are provided for the main switch in a wide range of load variations. Furthermore, the auxiliary circuit in the converter exhibits a short conduction duration, resulting in negligible conduction losses due to the minimal circulating current. Additionally, both the auxiliary switch and diode achieve zero‐current switching (ZCS), effectively eliminating switching loss. Moreover, the diode operates without reverse recovery issues, preventing any significant loss in the converter. These features have made it possible to design a converter with high voltage gain, high efficiency, and high power density. The fundamental operational principles of the converter are comprehensively elucidated, and an in‐depth analytical assessment of its steady‐state performance is conducted. In conclusion, a 200 W prototype has been implemented to validate the converter’s performance.